Fertigation for Vegetables: A Practical Guide for Small Fields - Jim DeValerio; David Nistler; Robert Hochmuth; Eric Simonne (EDIS)
More and more farmers are growing small crops of fruits and vegetables for specialty local markets. They commonly grow several crops at different stages of development at the same time, so they have a variety of produce to sell to customers. This forces farmers to make several fertilizer calculations because of their diverse crop demands, because water and nutrient requirements vary according to the crop and stage of development. This 7-page fact sheet helps growers correctly interpret fertilizer recommendations and calculate accurate fertilizer amounts to be used based on crop nutrient requirements. Written by Jim DeValerio, David Nistler, Robert Hochmuth, and Eric Simonne, and published by the UF Department of Horticultural Sciences, October 2012.